STUDENTS’ POSITIONAL IDENTITY IN ENGLISH WRITING - Setyaningrum, Riya Risqi (TELL - US JOURNAL, 2020)
Writing is the most difficult in English. The students have to master their vocabulary and grammar to make their writing correct. English as international languages for Indonesia students make their vocabulary is very lack, moreover in mastering their grammar. The Indonesian students have to study hard in writing English. In learning writing English, the students’ position have themselves as good writer and bad writer based on ethnicity, economic statues, gender, age, and education. So this study is present to know the students’ positional identity in English writing. The research method of study is descriptive qualitative. The data of study are students’ writing and interviews. The sample of study are students second semester of English Education Department at Lamongan Islamic University and Billfath University. It consists of 40 students both of University. Based on the study, the most of students have position their identity as good writer in writing English based on economic status and education. It means that economic status and education are the most influences in learning writing English in Indonesia. So, the English teachers have to think hard the way to improve the students’ writing in English in class.